Tinjauan Yuridis Perlindungan Hak Merek Dalam Perspektif Perbandingan Hukum Indonesia Dan Amerika Serikat - Yudhi Priyo Amboro; Steven Steven (Journal of Judicial Review, 2015)
Trademarks means any sign which is capable of distinguishing goods or services dealt with or provided in the course of trade that must be protected to prevent unfair competition, justice, public order and legal certainty. Registered trademarks has full rights to use the trademarks. Therefore considering the importance of trademark registration in the constitutive system, it is expected to trademarks user to register its marks in the Intellectual Property office in order to avoid lawsuits either criminal claims or compensation from another party. This study describes clearly and carefully about the similarities and differences of the provisions of trademarks in Indonesia and United States, how the protection of the law and the provisions of the state know which one is better in providing legal protection to trademarks holder.This research is a normative law by using the method of comparative law. The data used are secondary data. Performed with data mining literature (library research). Once all the data is collected, the data is then processed and analyzed, the qualitative analysis was used to group the data point by the studies aspects. Further conclusions drawn related to this study, then described descriptively.Based on the results of this study showed that there are some similarities and differences between Indonesia’s and United States’ provisions. But, judging from the legal protection to trademarks holder, United States’ trademarks law provides more protection instead of Indonesia’s, based on the further protection measures to protect the rights of its trademarks.